Pilgrimages as Community Processes: An Ethnography of the Pilgrims from the San Miguel and San Ignacio Neighborhoods in Iztapalapa (Andamios, Revista de Investigación Social, 2025)
Pilgrimages are groups formed through community social interaction via religious participation, with the purpose of transporting pilgrims to a sanctuary or sacred place to request shelter, protection, or express gratitude to a sacred image. These journeys are driven not only by people’s devotion and faith, but also by a sense of belonging to a community that is strengthened through shared participation in the celebration of the religious event. This article reflects on this phenomenon based on the ethnographic material collected, focusing on social relations based on the principle of reciprocity in pilgrimages in the San Miguel and San Ignacio neighborhoods of the Iztapalapa Municipality and the image of Christ Appeared, located in the Totolapan sanctuary. In addition, the organization, rituals, and their connection to the space –that is, to the journey taken by pilgrims to the sanctuary– are presented, all reinforcing the unity of the group and the communal references that shape the sense of community.
Keywords: Pilgrimage; sanctuary; community; collective identity